Analisis Penggunaan Aplikasi Sikesal 2 Dengan Menggunakan Metode System Usability Scale - Alvito Widianto; M Fikrul Hakimi; M Reihan Al Fajri; Yovi Pratama (TIN: Terapan Informatika Nusantara, 2023)
SiKesal 2 is an application used by the people of Jambi City to make it easier to report complaints such as damaged roads, clogged drains, social assistance, and so on. SiKesal 2 application still has some weaknesses, so it is necessary to do testing to measure the usability of the website. By analyzing Usability with 5 aspects, namely Learnability, Efficiency, Memorability, Errors and User Satisfaction. By using the 5 aspects, Based on the results of SUS analysis or (System Usability Scale) from the calculation of SUS questionnaire, the results of Acceptability / user acceptance are in the MARGINAL LOW category, the grade scale level is in the D category and, the adjective rating is in the OK category. It is hoped that this research will provide useful knowledge for developers with the perspective of SiKesal 2 application users